2019
DOI: 10.3390/antiox8100446
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of the Ethanol Extract of Illicium henryi against Acute Liver Injury in Mice Induced by Lipopolysaccharide

Abstract: The root bark of Illicium henryi has been used in traditional Chinese medicine to treat lumbar muscle strain and rheumatic pain. Its ethanol extract (EEIH) has been previously reported to attenuate lipopolysaccharide (LPS)-induced acute kidney injury in mice. The present study aimed to evaluate the in vitro antioxidant activities and in vivo protective effects of EEIH against LPS-induced acute liver injury (ALI) in mice as well as explore its molecular mechanisms. The mice were injected intraperitoneally (i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Two recent in vivo studies confirmed the effects of the Ethanol extract (EEIH) of Illicium henryi (EEIH) on LPS-induced acute liver and kidney injury and acute kidney injury in mice (185,186,212). The first study, which has focused on LPS-induced AKI in mice, showed that EEIH significantly decreased serum creatinine and blood urea nitrogen rates in mice.…”
Section: Illicium Henryimentioning
confidence: 90%
See 1 more Smart Citation
“…Two recent in vivo studies confirmed the effects of the Ethanol extract (EEIH) of Illicium henryi (EEIH) on LPS-induced acute liver and kidney injury and acute kidney injury in mice (185,186,212). The first study, which has focused on LPS-induced AKI in mice, showed that EEIH significantly decreased serum creatinine and blood urea nitrogen rates in mice.…”
Section: Illicium Henryimentioning
confidence: 90%
“…Studies have shown that oral administration of Ginsenoside significantly inhibits the expression of IL-1β and TNF-α in LPS-induced systemic inflammation and TNBS-induced colitis (179,(184)(185)(186). An in vivo study demonstrated that Ginsenoside down-regulates the NF-κB pathway in TNBS-treated mice (179).…”
Section: Ginsenosidementioning
confidence: 99%
“…It is well-known that nitrosative stress is implied in the liver pathophysiology [ 40 ]. In particular, peroxynitrite accumulation in LPS-treated mice is one of the commonest causes for acute liver injury [ 41 , 42 ]. In fact, hepatocytes respond to LPS treatment with IL-6- and TNF-α-mediated NO production, which induces a hepatic acute phase response [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, four articles (i.e., two papers from Toczewska et al [3,4], Maciejczyk et al [5] and Bourgonje et al [6]) describe the role of specific redox biomarkers as clinical outcomes of diseases and, concomitantly, examine their putative value in disease diagnosis. Furthermore, Bouroutzika et al [7], Matute et al [8] and Islam et al [9] demonstrate the beneficial properties of endogenous antioxidant compounds and phytochemicals on physiological processes, as well as their ability to protect from toxic agents and stressors, associated with oxidative stress induction. Finally, Karydas et al [10] describe the development of a novel multi-parametric system for the effective assessment of fruit antioxidant content, giving clues regarding precision farming.…”
mentioning
confidence: 99%
“…Towards this direction, they stressed that three phenolic compounds, specifically kaempferol, epigallocatechin gallate and peonidin-3-O-glucoside, appear to be probably the main contributors of the vasorelaxing action observed during fruit juice consumption. Additionally, Islam et al [9] have appraised the protective properties of a traditional Chinese medicinal plant, namely Illicium henryi, against the lipopolysaccharide-induced acute liver damage in a murine model. The results of their study suggested that the therapeutic efficacy of the corresponding plant extract, which also exerted in vitro antioxidant activities, was attributed to the upregulation of Nrf2 and the downregulation of TLR4/NF-κB signaling pathways, hence providing hepatoprotection against oxidative damage and inflammation.…”
mentioning
confidence: 99%